2021
DOI: 10.32771/inajog.v9i3.1339
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Antenatal Care Quality in Cases of Referred Pregnant Women in Emergency Rooms Based on MCH Book Records

Abstract: Objective: To determine the quality of antenatal care received by pregnant women, and perceptions of pregnant women and antenatal care providers regarding antenatal care.Method: A quantitative and qualitative study of cases of referred pregnant women in the Emergency Room (ER) of Dr. Cipto Mangunkusumo Hospital (RSCM) from 2017–2018 was conducted. Quantitative data was obtained by assessing the overall completeness of filling in the Maternal Child Health (MCH) book used to report the antenatal care received by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
3
0
0
Order By: Relevance
“…The results of the study also found that respondents aged < 20 years were 2.8% and respondents aged > 35 years were 17.6%. This is in line with research conducted by Ocviyanti and Sari, in 2021, namely in the case of referrals to pregnant women at emergency room RSCM there were 9.1% of respondents aged <20 years and 19.5% of respondents aged >35 years (Ocviyanti et al, 2021). At a young age, a woman's reproductive organs are not completely perfect and their mental development is not yet mature so they are not ready to become a mother and accept pregnancy where which can result in obstetric complications that can increase maternal mortality (Untari & Sehmawati, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of the study also found that respondents aged < 20 years were 2.8% and respondents aged > 35 years were 17.6%. This is in line with research conducted by Ocviyanti and Sari, in 2021, namely in the case of referrals to pregnant women at emergency room RSCM there were 9.1% of respondents aged <20 years and 19.5% of respondents aged >35 years (Ocviyanti et al, 2021). At a young age, a woman's reproductive organs are not completely perfect and their mental development is not yet mature so they are not ready to become a mother and accept pregnancy where which can result in obstetric complications that can increase maternal mortality (Untari & Sehmawati, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Dr. M. Djamil namely severe preeclampsia 23.1%, placenta previa 17.6%, and PROM 13.9%. This is in line with research conducted in the emergency room (ER) RSCM in 2021, which stated that severe preeclampsia was the most frequently established diagnosis, which was 32% (Ocviyanti et al, 2021). The incidence of hypertensive disorders of pregnancy increased from 16.30 million to 18.08 million globally, with a total increase of 10.92% from 1990 to 2019 (Wang et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation